Clinicopathology, Penile, SCC CLINICOPATHOLOGICAL CHARACTERISTICS OF PENIS SQUAMOS CELL CARCINOMA AT PROF. Dr. I G.N.G. HOSPITAL DENPASAR BALI 2016-2020 - Lisanthoni, Johnathan; Winarti, Ni Wayan; Sriwidyani, Ni Putu; Dewi, I Gusti Ayu Sri Mahendra (E-Jurnal Medika Udayana, 2024)
Penile cancer has an incidence range of 1% of all cancers in men. The most common type of penile cancer is squamous cell carcinoma (SCC). Objective : To determine the clinicopathological characteristics of penile squamous cell carcinoma at Prof I G.N.G.Ngoerah Hospital, Denpasar in 2016-2020 based on age, histologic subtype, histological grading, tumor size, pT stage, lymph node metastasis, and lymphovascular invasion. Methods : This study is a descriptive observational study of 78 cases of penile SCC at Prof I G.N.G.Ngoerah Hospital Denpasar for the period 2016 to 2020. The sample that were obtained from secondary data is cross-sectional (cross sectional) with total sampling technique, which uses patient medical record data at the Anatomical Pathology Installation. Prof I G.N.G.Ngoerah Hospital, Denpasar. Results : The most cases of penile SCC in this study were found in the 51-60 year age group (34.6%) with the usual type of SCC histological subtype (73,1%), grade II (61.5%), tumor size between 5 to 10 cm (35.9 %), pT2 stage (25.6%), negative lymph node metastasis (34.6%) and negative lymphovascular invasion (35.9%).